2022
DOI: 10.3389/fpls.2022.828321
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Time-Course Transcriptome and Co-expression Network Analyses Identify Salt Stress Responding Mechanisms in Chlamydomonas reinhardtii Strain GY-D55

Abstract: It is highly necessary to understand the molecular mechanism underlying the salt stress response in green algae, which may contribute to finding the evolutionary cues of abiotic stress response in plants. Here, we reported a comprehensive temporal investigation of transcriptomes using data at eight different time points, from an early stage (2 h) to a late stage (up to 96 h) in Chlamydomonas reinhardtii GY-D55 cells. The principal component analysis (PCA) of transcriptome profiles showed that the samples of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…2a ) based on the use of fluorescent reporters to mark these compartments 18 and starch staining 19 . In agreement with previous transcriptomic analyses using different Chlamydomonas strains (GY-D55 and CC-503) and solute concentrations 20 , 21 , we found that Chlamydomonas accumulates glycerol and proline as the main compatible osmolytes during stress. Interestingly, our time-course data suggests an earlier role for glycerol 15–60 min after stress, while proline may have a later role, since induction of proline metabolic gene transcription is not observed until 6 h after stress is applied (Fig.…”
Section: Resultssupporting
confidence: 92%
“…2a ) based on the use of fluorescent reporters to mark these compartments 18 and starch staining 19 . In agreement with previous transcriptomic analyses using different Chlamydomonas strains (GY-D55 and CC-503) and solute concentrations 20 , 21 , we found that Chlamydomonas accumulates glycerol and proline as the main compatible osmolytes during stress. Interestingly, our time-course data suggests an earlier role for glycerol 15–60 min after stress, while proline may have a later role, since induction of proline metabolic gene transcription is not observed until 6 h after stress is applied (Fig.…”
Section: Resultssupporting
confidence: 92%